EXPLORING PRE-SERVICE ENGLISH TEACHERS' COURSE EXPECTATIONS AND THEIR REALIZATION LEVELS THROUGH PORTFOLIOS - Şevki Kömür; Şeyda Selen Çimen (Informascope, 2017)
The purpose of the present study is to explore the expectations of pre-service English teachers from a course at the beginning of the term and realization levels of their expectations at the end as well as investigating the function of portfolios as an assessment tool from pre-service teachers' points of view. The participants were 90 third-year pre-service teachers, who took the Teaching Language Skills I, and developed portfolios during the fall term, 2016-2017 Academic year. The data were obtained from the portfolios and semi-structured interviews and they were analyzed by using content analysis technique. The results revealed that pre-service English teachers expected to be trained in four different categories during the course Teaching Language Skills I, which are skills teaching, managing learning and teaching, course design, and teacher skills. It was also found that 60% of the expectations of pre-service English teachers were met by the course. Pre-service teachers also reported that they benefited from the course Teaching Language Skills I in terms of some aspects of language teaching without expecting to do so. Keywords: portfolio assessment, language teacher education, teaching language skills, course expectations.